Creating the Client Who Can Create Himself and His Own Fate – the Tragedy of the Citizens’ Contract - Andersen, Niels Åkerstrøm (Qualitative Sociology Review, 2007)
This article is about the emergence of new forms of active citizenry, empowerment, and self-help that meet in the so-called citizens’ contract. Based on Danish social policy, the article shows how the articulation of the citizen as ‘fellow citizen’ has led to the current contractualization of the relationship between the administration and the individual citizen. Citizens’ contracts are employed not only to commit clients to a specific behavior, but first and foremost to commit them to a particular inner dialogue about obligation and freedom. Economic assistance becomes dependent on this dialogue and they thus become contracts both between the administration and the citizens and between the citizens and their own selves. The article moves beyond the Foucault-inspired categorization by identifying the tragic consequences of these self-contracts.